On boundedness of integral means of Blaschke product logarithms - Vasylkiv, YA. V.; Kondratyuk, A. A.; Tarasyuk, S. I. (Mathematical Modelling and Analysis, 2003)
Using the Fourier series method for the analytic functions, we obtain a result characterizing the behaviour of the integral means of Blaschke product logarithms. Namely, if the zero counting function n(r, B) of the Blaschke product B satisfies the conditionwhere l is a positive function on (0, 1) such thatthen the q‐integral mean mq (r, log B) = [] is bounded on (0,1), where log B is a branch of the logarithm of B. Šiame straipsnyje Furje eilučių metodu gauta analitinių funkcijų Blaschke sandaugos logaritmų integralinių reikšmių elgsenos charakteristika. Jeigu Blaschke sandaugos B nulių funkcija n(r, B) tenkina sąlygą [], čia l yra neneigiama funkcija intervale (0,1) ir [], tuomet q‐integralinė reikšmė [] yra aprėžta intervale (0,1), kai log B yra B logaritmo šaka. First Published Online: 14 Oct 2010